No genomic mosaicism in a putative hybrid butterfly species (2007)
Recent descriptions of hybrid animal species have spurred interest in this phenomenon, but little genomic data exist to support it. Here, we use frequency variation for 657 amplified fragment length polymorphism (AFLP) markers and DNA sequence variation from 16 genes to determine whether the genome of Heliconius pachinus, a suspected hybrid butterfly species, is a mixture of the putative parental species, Heliconius cydno and Heliconius melpomene. Despite substantial shared genetic variation among all three species, we show that the genome of H. pachinus is not a mosaic; both AFLP and DNA sequence data overwhelmingly associate H. pachinus with just one of the potential parents, H. cydno. This pattern also applies to the gene wingless, which is tightly linked to the locus that determines forewing colour-one specific H. pachinus trait that has been hypothesized to have originated from H. melpomene. As a whole, the data support a traditional, bifurcating model of speciation in which H. pachinus split from a common ancestor with H. cydno without a genetic contribution from H. melpomene. However, comparison of our data to DNA sequence data for another putative hybrid Heliconius species, Heliconius heurippa, suggests that the H. heurippa genome may be a mosaic.